ANALISIS NILAI-NILAI MANAJEMEN BISNIS SYARIAH PENGARUH PAJAK BUMI BANGUNAN DAN RETRIBUSI DESA TERHADAP PENDAPATAN ASLI DAERAH DESA (STUDI DI DESA PURASARI, KECAMATAN LEUWILIANG, KABUPATEN BOGOR PERIODE 2016-2019) - Suryadi; Tubagus Rifqy Thantawi; Hasbi Ash Shiddieqy (SAHID BUSINESS JOURNAL, 2022)
This study aims to explain the Analysis of Islamic Business Management Values Regarding the Effect of Land and Building Taxes and Village Levies on Local Revenue in Purasari Village. This research is limited to analyzing annual quantitative secondary data in the time span between 2016-2019. The data is reprocessed according to the needs of the model used. Sources of data come from various sources, including the regional revenue office statistics, scientific journals and other literature related to this research topic. The analytical method used in this research is a simple analysis which is used to determine the extent of the effect of changes in another variable with the help of SPSS. The results showed that land and building taxes and levies have a positive and significant effect on local revenue.